O Programa de Reabilitação Profissional do Instituto Nacional do Seguro Social e a reinserção do trabalhador no mercado de trabalho: um estudo de caso - Santos, Geovana de Souza Henrique dos (Universidade Federal de São Carlos, 2015)
Currently, in Brazil, the assistance geared to workers who were affected by disease or accident, who find themselves unable to return to their original function, but have the potential to exercise other labor activities, is provided by the National Institute of Social Security (INSS) to taxpayers, through the Vocational Rehabilitation Program (PRP). Vocational rehabilitation aims to provide the necessary means for the worker s re-entry into the labor market. This research aimed to understand the INSS PRP s contribution to the employee s reintegration in the market and, as specific objectives, identify the profile of the population served by the program of the Social Security Agency (APS) of the Southeast, between 2007-2012; we investigated the means used within the program to reintegrate workers into the labor market; trace the professional profile of users who visited the PRP; and characterize, in the view of the rehabilitated workers, how the program interfered with their reintegration into the market. This is a case study because it was focused on a single APS among a vast universe, transversal and descriptive, which had as data collection 592 records of people referred to the PRP on the above period; besides having been performed eight in-depth interviews with workers considered rehabilitated. The results showed that the profile of the people served corresponds to 76.5% male, 61.15% of those aged between 30-44 years, the most natural of the host city of the Program or the same state, about 62 % are married or living in a stable relationship, 15% have some form of disability, 42% had not finished elementary school, 74.5% are affiliated to the INSS as employees, 99.5% receive social security benefits, and of these, 77,2% receive common sickness assistance. About 48.5% of people referred were eligible to join the program. As for the resources used in the rehabilitation process, in 5.33% of cases was fitting, 23.33% in the provision of courses, and 25% training in the bond company; no resource were used with the remainder. Workers considered rehabilitated by the organization totaled 34%; currently, according to information from corporate systems of the institution, of these, 49.02% are employed or are self-employed, Social Security contributors, and 26.5% are without bond. The in-depth interviews allowed us observe that the rehabilitated workers do not show a direct relationship between the program and their reintegration into the labor market, but they claim that the resources used in the rehabilitation process are important means to win, if not a job, at least recognition personal and The study points to the need for coordination between the INSS and companies to be forwarded to the rehabilitated internship or a job vacancy by the Institute; this, while federal agency, would have, in their view, the power to promote this articulation and guarantee them a job. The PRP requires changes, a more active attitude of the body at the end of the rehabilitation process, and fundamentally have not ceased their responsibility at the time the rehabilitation of the certificate is sent out.
Keywords: Reabilitação profissional; Instituto Nacional do Seguro Social (Brasil); Incapacidade laborativa; Reinserção no mercado de trabalho; Retorno ao trabalho; Vocational rehabilitation; National Institute of Social Security; Employment incapacity; Reinsertion in the labor market; Return to work; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL